Infection dynamics across the dry period using Dairy Herd Improvement somatic cell count data and its effect on cow performance in the subsequent lactation - Lipkens, Z.; Piepers, S.; Verbeke, J.; De Vliegher, S. (Journal of dairy science, 2019)
In this study, we studied infection dynamics across the dry period using test-day somatic cell count (SCC) data from 739 Holstein cows from 33 randomly selected commercial dairy herds in Flanders, all of which applied blanket dry-cow therapy at dry-off. First, we determined infection dynamics, combining the last test-day SCC before dry-off and the first test-day SCC after calving. Next, we determined the effect of dry period infection dynamics, adjusting for the level of the second test-day SCC after calving, on the evolution of test-day SCC and milk yield (MY) and on clinical mastitis and culling hazard in the subsequent lactation. Using an SCC threshold of 200,000 cells/mL, 12.6% of the cows considered healthy before dry-off acquired a new intramammary infection (IMI) across the dry period, whereas 66.9% of the cows considered infected before dry-off cured from IMI. Infection dynamics across the dry period significantly affect a cow's SCC, clinical mastitis risk, and culling hazard in the subsequent lactation. Cows with a new IMI, a cured IMI, or a chronic IMI across the dry period had higher test-day SCC than healthy cows, and their test-day SCC evolved differently over time. This was not the case for test-day milk yield, for which no association with infection dynamics was detected. Furthermore, cows with a second test-day SCC <200,000 cells/mL had a lower test-day SCC in the remainder of the lactation than cows with a second test-day SCC ≥200,000 cells/mL, but this association was modified by infection dynamics across the dry period. The lowest test-day SCC in the remainder of the lactation was observed for cows that remained healthy across the dry period combined with a low (<200,000 cells/mL) second test-day SCC. Cows that cured from an IMI present at dry-off and cows with a chronic IMI across the dry period were more likely to develop clinical mastitis (hazard ratio = 2.22 and 2.89; 95% confidence interval = 1.45–3.43 and 1.60–5.20, respectively), and chronic IMI cows were more likely to be culled (hazard ratio = 3.68; 95% confidence interval = 1.64–8.20) in the subsequent lactation compared with healthy cows. This was not true for cows that became infected across the dry period. This study underlines the importance of good udder health management during lactation to prevent IMI at dry-off rather than curing infected cows during the dry period to ensure optimal udder health in the subsequent lactation.